Exploring mTOR inhibition as treatment for mitochondrial disease. Issue 9 (6th August 2019) - Sage‐Schwaede, Abigail; Engelstad, Kristin; Salazar, Rachel; Curcio, Angela; Khandji, Alexander; Garvin Jr, James H.; De Vivo, Darryl C.
Abstract: Leigh syndrome and MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke‐like episodes) are two of the most frequent pediatric mitochondrial diseases. Both cause severe morbidity and neither have effective treatment. Inhibiting the mammalian target of rapamycin (mTOR) pathway has been shown in model mice of Leigh syndrome to extend lifespan and attenuate both the clinical and pathological progression of disease. Based on this observation, we treated two children with everolimus, a rapamycin analogue. The child with Leigh syndrome showed sustained benefit, while the child with MELAS failed to respond and died of progressive disease. We discuss possible mechanisms underlying these disparate responses to mTOR inhibition.